ANALYSIS OF MATERIAL TEACHING BIOLOGICAL NEEDS BASED SSCIENCE PROCESS SKILL STUDENTS - Sulis Anjarwati (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2015)
Student learning activities at school is important to note. Maximum results are expected to be achieved by students during the learning process. Teachers have an important role in monitoring learning activities to the results obtained by students. Good results will be accepted if the process is also running well and smoothly. The process that students do not all directed by the teacher because it is expected students have their own skills in developing the mindset and improve creativity, so that teachers act as mediators and facilitators. The low skill of science process students of SMP / MTs Kota Metro and SMP Negeri 1 Gedung Aji needs to get the attention of the teacher especially in science biology lesson. So the steps that can be done by the teacher one of them is developing science teaching materials Biology-based skills science process.